The Effect of Implementing Google Classroom-Based Learning Innovations and Technology Support on Learning Performance of Economics Faculty Students at Medan State University - Raihan, Muhammad; Syahreza, Dina Sarah; Putri, Nada Deliza; Sianturi, Reni Marlina; Napitupulu, Putra Jhonatan Mula Jaya; Siahan, Tabhita Berliana (Economic: Journal Economic and Business, 2024)
This study aims to analyze the influence of the implementation of Google Classroom-based learning innovation and technological support on student learning performance in the Faculty of Economics, Universitas Negeri Medan. The research method used was a quantitative approach with a sample of students from the Faculty of Economics, Universitas Negeri Medan. The results show that the implementation of Google Classroom-based learning innovation and technological support have a positive and significant effect on student learning performance. These findings indicate that the use of online learning platforms such as Google Classroom, supported by the availability of adequate technology, can improve students' academic performance. The implication of this research is the need to improve lecturers' ability to utilize learning technologies, as well as the provision of adequate facilities and infrastructure to support online learning at the Faculty of Economics, Universitas Negeri Medan. This study provides insights for educational institutions in developing effective learning strategies through the integration of digital technology.